2019
DOI: 10.1186/s12870-019-1759-1
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association analysis for fumonisin content in maize kernels

Abstract: Background: Plant breeding has been proposed as one of the most effective and environmentally safe methods to control fungal infection and to reduce fumonisin accumulation. However, conventional breeding can be hampered by the complex genetic architecture of resistance to fumonisin accumulation and marker-assisted selection is proposed as an efficient alternative. In the current study, GWAS has been performed for the first time for detecting high-resolution QTL for resistance to fumonisin accumulation in maize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 82 publications
2
23
0
Order By: Relevance
“…The plant material was obtained from the North Central Regional Plant Introduction Station from Iowa State University following the seeds import law applicable for Spain. The list of inbred lines used in this study along with their accession identifications at the North Central Regional Plant Introduction Station (NCRPIS) is available as additional file in Samayoa et al [59].…”
Section: Methodsmentioning
confidence: 99%
“…The plant material was obtained from the North Central Regional Plant Introduction Station from Iowa State University following the seeds import law applicable for Spain. The list of inbred lines used in this study along with their accession identifications at the North Central Regional Plant Introduction Station (NCRPIS) is available as additional file in Samayoa et al [59].…”
Section: Methodsmentioning
confidence: 99%
“…So far, there is just one GWAS on resistance to fumonisin accumulation, which has confirmed that highly significant genotype × environment interaction as well as genetic variation for many genes with small effects would contribute to the high complexity of the inheritance of maize resistance to kernel contamination [ 69 ]. In the inbred panel of approximately 250 entries, 39 SNPs, clustered into 17 QTL, were significantly associated with resistance to fumonisin accumulation in maize kernels.…”
Section: Genome-wide Association Studies For Fer and Fumonisin Conmentioning
confidence: 99%
“…Moreover, in order to develop genetically resistant germplasm to Fusarium researchers carried out Quantitative Trait Locus (QTL) mapping analysis and GWAS by testing several distinct population structures (McMullen et al 2009;Yang et al 2010;Zila et al 2013Zila et al , 2014Warburton et al 2013;Chen et al 2016;Ju et al 2017;Maschietto et al 2017;Gaikpa and Miedaner 2019;Samayoa et al 2019;Septiani et al 2019).…”
Section: Introductionmentioning
confidence: 99%